The Relationship Between Sexual Knowledge and Marital Forgiveness With Mental Health of Married Women - nesa samaeilvand; banafshe hasanvand (Iranian Association of Health Education and Health Promotion, 2015)
Background & objective: An appropriate sexual intercourse resulting in both parties' satisfaction can play a crucial role in couples' relations and family strength. Forgiveness is one of the psychological and relational processes for enhancing hurt-healing which influence many indicators of mental health. Women' mental health guarantees family and, in turn, society's health. Thus, this study aims to explore the relationship between sexual knowledge and marital forgiveness with the mental health of married women aged 20-40 yrs. in Aleshtar city in Lorestan Province, Iran . Methods:The Hooper Sexual knowledge scale, Pollard Forgiveness scale (FFC), and Goldberg General Health Questionnaire (GHQ-28) were used in the study. The statistical population consisted of married women in Aleshtar city in the year 2012. Samples comprised of 120 people were selected by clustering sampling. Data was analyzed through SPSS16 using simple correlation coefficient regression and t-test were used for comparing means and analysis of variance. In this study, the significance level was considered 0.05. Results: There was a significant positive correlation between sexual knowledge and mental health of married women (r=0.215, p <0.05). There was also was a significant positive correlation between forgiveness and mental health of married women (r=-0.347, p <0.001), Conclusion: Education and increasing the sexual knowledge of women could improve their mental health. In addition, forgiveness has a positive role in improving the mental health of married women. Paper Type: Research Article.